Organisational intervention on absenteeism among workers: a systematic review - Nur Adibah Mat Saruan,; Hanizah Mohd.Yusoff,; Sharifa Ezat Wan Puteh,; Mohd Fadhli Mohd Fauzi,; Mohd Rizal Abdul Manaf, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Sickness absenteeism is increasing in trend mostly due to being overworked and fatigue that leads to increasing number of work-related injuries, which further disrupt the quality of care and the revenue of an organization. Absenteeism can be overcome by effective organisational intervention at the workplace. Therefore, this review was aimed to identify the important component in an organisational intervention to reduce absenteeism at work. Systematically, articles were searched from PubMed (PMC), Science Direct, Scopus (SciVerse) and Sociological Abstracts (ProQuest) from June 2013 to June 2018 using specific keywords. The input revealed 12 articles, including studies that measured absenteeism as the outcome regardless of working categories except for outdoor workers. Studies that involved all the domains in the intervention which were workplace environment, motivation and individual factors had given significant results in reducing absenteeism. Hence, the intervention at organisational level must use a comprehensive approach to ensure the target of reducing absenteeism at workplace is achieved and become sustainable.